The story continues: recent advances on the life and death of the Pleistocene cave bear. (21st April 2019) - Figueirido, Borja; van Heteren, Anneke H.
ABSTRACT: In this issue, we cover an exceptional topic in Vertebrate Paleobiology that has been an enjoyable challenge for scientists and the popular media alike: the life and death of the Pleistocene cave bear (Ursus spelaeus). As an icon of the ice-age, the cave bear inhabited the glacial ecosystems of Eurasia, and it was the inspiration of a popular book written in 1976 by Björn Kurtén, entitled The cave bear story: life and death of a vanished animal. Although 'The life and death' was a summary of the knowledge acquired on cave bear biology at that time, four decades later, many aspects of its palaeoecology, extinction and evolution are still a matter of debate. With this volume, we aim to bring together the most recent research on cave bear biology in order to provide an update on the palaeoecology, biogeography, systematics, and phylogeny of this recently extinct ursine bear. We thus organised a symposium on the 1st of August 2017 as part of the three-day Annual Meeting of the European Association of Vertebrate Palaeontologists (EAVP) in Munich, Germany, that was an additional opportunity to announce the volume and to discuss this exciting subject face-to-face among specialists.